Analysis of Vocational School Students' Error in Solving Linear Program Problems - Enjang Jaenal; Harry Dwi Putra; Asep Ikin Sugandi; Heris Hendriana (IKIP Siliwangi, 2023)
The reality on the ground shows that students still make mistakes in solving problems in the form of Linear Program stories. This study aims to describe students' mistakes in solving word problems in linear programming material. The method used in this research is descriptive qualitative research. The subjects in this study were class X students of Karya Bahana Vocational School, Bekasi City. The instrument in this study was in the form of 5 questions in the form of descriptions. In addition to the instrument in the form of tests, interviews were used to dig deeper into students' answers to the questions presented. The results showed that the most errors made by students were in the aspect of errors in writing the final answers, and the fewest errors were in the aspects of transformation errors. The cause of reading errors is that students are unable to interpret sentences correctly and cannot find key words and important information. The cause of the error in understanding the problem was that students did not include the known data and the data asked. The causes of errors in the transformation are students not being able to model everyday sentences into mathematical symbols and errors in using mathematical operations. The cause of the process skill error was that the student was unable to write down the objective function and the student was unable to continue with the answer, while the cause of the error in writing the final solution was the inability of the student to draw conclusions correctly.